Answer Checking Techniques, Scoring, Value Conversion, And Assessment Standards In Religious Education Subjectsj - Ahmad Nurfauzan, Ahmad; Nurfauzan, Ahmad (Noor: Journal of Islamic Studies, 2025)
This study aims to determine the technique of checking answers, scoring, value conversion, and assessment standards in Islamic religious education subjects using a qualitative approach through literature studies to explore strategies for improving the quality of learning evaluation, including correction methods, scoring techniques, value conversion processes, and the importance of assessment standards. The findings indicate that the application of analytical rubrics, dual scoring systems, and digital technology can help improve the reliability and objectivity of assessments. Variations in scoring and conversion methods—either linear, percentile, norm-based, or criterion-based—require alignment with national standards so that the final results reflect students' abilities fairly and meaningfully. Structured and consistent assessment standards have proven to be an important foundation in ensuring the quality and accountability of assessments. This study recommends improving educator training, ongoing socialization, and systematic evaluation to strengthen the application of assessment standards in supporting a transparent and quality-oriented evaluation system for education.